The Effective Financing Model of Koperasi Sharia in the Covid 19 Pandemic Era - Taufan Maulamin; Erni Prasetiyani; Martina Safitri (Budapest International Research and Critics University, 2021)
The COVID-19 pandemic has not ended, causing some Low and Small business affected by COVID-19 to stop their operations, uncertainty around. It is stopped due to lack of capital or lack of consumers. Therefore. This research provides an effective financial inclusion model that reaches all levels of society with a smaller scope. The research method is :1. A qualitative participant observation where the researcher is directly involved in overseeing the establishment of cooperatives and managing the daily operations of all-business sharia cooperatives. 2. Starting from setting up the registration form, calculating the profit-sharing formula for capital loans (Mudharabah) and financing loans (Murabahah) in addition to compiling financial reports and calculating profit sharing for each member proportionally. In addition to mudharabah and murabahah products, the cooperative also provides a social fund (Qordhul Hasan/benevolence fund) of 20% of the profits received from loan transactions. These funds are used for loans without any profit in it. This fund was formed as a loan to members who need social funds such as medical treatment, education, childbirth and others. Due to the (still in) pandemic period, cooperative members are still a small number of the population in this region.